Perceptions of Social Media-Based Microlearning in Enhancing Interest and Retention in Japanese Language Learning among Interns to Japan - Rita Agustina Karnawati; Aisyah Jingga Framesti (STAI Hubbulwathan Duri, 2025)
Effective learning strategies are essential for mastering foreign languages, especially Japanese, which presents structural and cultural complexities. This study investigates the perceptions of prospective interns to Japan regarding the use of social media-based microlearning to enhance their interest and retention in Japanese language learning. A quantitative survey design was employed involving 150 prospective Japanese interns selected through cluster sampling. Data were collected using a Likert-scale questionnaire designed to measure learning interest and retention. The instrument's validity was assessed using the Aiken index, while reliability was confirmed through Cronbach’s alpha (interest = 0.869; retention = 0.904). Data analysis included descriptive statistics, normality testing, and simple linear regression to examine the relationship between learning interest and retention. The findings revealed a significant positive correlation between learning interest and learning retention (r = 0.637, p 0.01), with interest accounting for 40.6% of the variance in retention. Most respondents demonstrated high levels of interest and retention, particularly among Generation Z learners. These outcomes suggest that microlearning via social media platforms supports both engagement and memory retention in language acquisition. Microlearning offers concise, accessible, and engaging content that aligns with the digital habits of modern learners. Its implementation in Japanese language education, particularly for internship preparation, can enhance learner motivation and long-term retention. The study recommends further exploration into content design, learner motivation, and digital engagement strategies to optimize microlearning outcomes in foreign language contexts.